Conicity Index of Adult Bangladeshi Population and their Socio-Demographic Characteristics - Flora, Meerjady Sabrina; Mascie-Taylor, CGN; Rahman, Mahmudur (Ibrahim Medical College Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> In spite of acknowledged importance, no unified definition exists for central obesity. Several anthropometric indexes such as waist circumference, waist-hip ratio, waist-to-height ratio, conicity index etc, are being used. Cindex has been shown to correlate well with various cardiovascular risk factors associated with visceral fat accumulation in some population. Data were collected through interviewing and measuring 22,995 adult males and females of an urban (Mirpur, Dhaka City) and rural area (Kaliganj sub-district) in 2002 and 2003. Overall the mean (SD) conicity index was 1.20 (0.10) and 40.8% of this sample had a high Cindex. Females, increasing age, urban residents, Christians, the better educated, married and farmers were more likely to have higher Cindex than their counterparts. There is a scarcity of data about the conicity index of Bangladeshis and this cross-sectional study is the first large-scale attempt. So it can be used as a baseline data for further research in this field. Ibrahim Med. Coll. J. 2009; 3(1): 1-8 Key words: Conicity index, socio-demography, Bangladeshi doi: 10.3329/imcj.v3i1.2910